A Review of Renewable Energy Development and Planning for an Island Province in Eastern Indonesia: Case Study of North Maluku - Pinto Anugrah; Subhan Petrana; Heru Dibyo Laksono (Andalas Journal of Electrical and Electronic Engineering Technology, 2022)
Indonesia intends to use renewable energy both locally and on a national scale. Regional energy planning must be developed by provincial governments in accordance with national energy planning (RUEN). One of the few provinces that has already published its regional energy planning is North Maluku Province. The ambition to use more renewable energy technologies for power generation is already taken into account in their regional energy planning. However, North Maluku Province may rely on renewable energy as their primary source of power because of the abundance of these resources. The purpose of this paper is to examine renewable energy development and planning in relation to the RUPTL 2021-2030 power development plan. This review gives an insight that North Maluku Province still have untapped renewable energy potential which can be developed in the future to increase its renewable shares in electricity mix as well as to enhance energy security and accessibility in the region.